Figural Letters of Karion Istomin’s Illuminated ABC-books and the Western European Tradition of Figural Alphabets: Entertaining, Teaching, and Edifying - Savelieva, Maria Iu. (Actual Problems of Theory and History of Art, 2016)
This work is intended to help to get a better insight into the imagery of the illuminated ABC- books by Karion Istomin (three manuscripts and one engraved by Leonti Bunin) by comparing them with their predecessors from Western Europe — decorated alphabets of the late Middle Ages and Renaissance which contain figural (i.e. composed of figures) or historiated letters (as is the case of the lost alphabet from Berlin Kupferstichkabinett), or engraved letters of Master E. S., or the alphabet of Mary of Burgundy from the Louvre). As far as we know, the initials of Karion’s ABC-books still require a detailed research, and our basic intention is to understand their iconography and their meaning. After an excursus on the use of the ABC-books, the author refers to a number of their initials. The study of the imagery of the figural letters suggests that these figures were not simply born of formal fantasies. Many of them were introduced with an edifying moralizing purpose, which can be confirmed by comparing Istomin’s work with relevant Western artifacts or reading his own verses that accompany each letter. Even though his style is extremely florid, the Christian basis of his pedagogical principles is shown very clearly. These primers reflect the structure of the Christian universum; they provide both instruction and edification while doing it in a playful visual manner, which was unique for that time.